2015
DOI: 10.1038/ng.3175
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis identifies genes and evolutionary forces driving gastrointestinal tract tumor progression

Abstract: To provide a more comprehensive understanding of the genes and evolutionary forces driving colorectal cancer (CRC) progression, we performed Sleeping Beauty (SB) transposon mutagenesis screens in mice carrying sensitizing mutations in genes that act at different stages of tumor progression. This approach allowed us to identify a set of genes that appear to be highly relevant for CRC and to provide a better understanding of the evolutionary forces and systems properties of CRC. We also identified six genes driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
129
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 60 publications
6
129
2
Order By: Relevance
“…In addition, in many cases, only a single transposon insertion was present at a CCG in tumor cells, suggesting that many CCGs are functioning as haploinsufficient TSGs. This is similar to what has been observed in other SB mutagenesis screens performed in solid tumors (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Csupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, in many cases, only a single transposon insertion was present at a CCG in tumor cells, suggesting that many CCGs are functioning as haploinsufficient TSGs. This is similar to what has been observed in other SB mutagenesis screens performed in solid tumors (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Csupporting
confidence: 90%
“…New technologies that would provide a more complete understanding of the genetics of TNBC are still needed to deconvolute the complexity of this deadly cancer. Our laboratory and others have pioneered the use of transposon mutagenesis in mice as a tool for cancer gene discovery (18)(19)(20)(21)(22)(23)(24)(25)(26). Transposons induce cancer by randomly inserting into the mouse genome, mutating, and disrupting potential cancer genes.…”
mentioning
confidence: 99%
“…Transposon insertion sites were sequenced using splinkerette PCR to produce barcoded PCR products, which were then pooled and sequenced (22)(23)(24). To obtain the maximum amount of sequencing reads and avoid PCR bias (29), we used Illumina sequencing and acoustic shearing of genomic DNA (gDNA).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that most CCGs identified by SB mutagenesis function during late stages of tumor progression (24). To identify the subset of CCGs that function early in tumor development, we selected transposon insertion sites represented by ≥100 sequencing reads, arguing that these insertions would be present in the largest number of tumor cells.…”
Section: Identification Of Ccgs Driving the Development Of Mesenchymalmentioning
confidence: 99%
See 1 more Smart Citation